Studying the Relationship Between Gestational Age, Sepsis, and the Occurrence of Thrombocytopenia in Newborns in Al-Marj City in Libya from January 2022 to December 2023 - Rabeaa Mohammad Saleh; Nowara Abu Zaid Abdulgader; Najwa Ayad Saad Al-Aqili (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aimed to analyze the relationship between gestational age and the incidence of sepsis (blood infection) accompanied by thrombocytopenia in newborns in the city of Al-Marj, in addition to identifying other factors that may increase the risk of infection such as sex, birth weight, blood type, delivery method and the health status of mothers. The study included a sample of 35 newborns from Al-Marj Teaching Hospital. The small sample size is attributed to the fact that thrombocytopenia is a rare and not widely prevalent condition. Data were collected from January 2022 to December 2023. Blood samples were taken from the newborns and a questionnaire was completed at the time of sample collection. The data were then analyzed using the Statistical Package for the Social Sciences (SPSS), calculating frequencies and percentages and performing a Chi-square test. The results were considered statistically significant if the P-value was less than 0.05. This study reveals a statistically significant relationship between gestational age and sepsis with thrombocytopenia making newborns more vulnerable. Additionally, other factors such as sex, low birth weight, cesarean delivery and blood groups (A+ ,B+ and O+) contribute to thrombocytopenia in newborns.